Cross-Sectional Capacities of Reinforced Concrete Structures Using Abaqus and Staadpro Software - Rizaldi Al Kahfi; Faris Rizal Andardi; Yunan Rusdianto; Sandi Wahyudiono (Universitas Islam 45, 2024)
The Faculty of Computer Science building at Universitas Brawijaya is classified as a category II building because it is located in an earthquake-prone area so it is included in seismic design B. The building’s planning adheres to the regulations of SNI 2847:2019 and SNI 1727:2020. Software is required to efficiently and accurately analyze the forces acting on a structure. Generally, there are two main directions for software: structural design or planning, and research. Both design and research software are used as powerful analytical tools to solve complex problems such as structural behavior. The objective of this research is to analyze the cross-sectional capacity of the Faculty of Computer Science building at Brawijaya University using Abaqus and Staadpro software. The redesign process begins by analyzing the earthquake structure to be applied. Using the equivalent static analysis method, the redesign of this building involved obtaining design results for floor plates with dimensions of 120 mm, roof plates with dimensions of 100 mm, main beams measuring 300 x 600 mm, secondary beams with dimensions of 250x500 mm, and columns with dimensions of 600x600 mm. The analysis results of the cross-sectional capacity meet the criteria for special moment frame systems (SRPMK), specifically the Strong Column Weak Beam concept, are shear resistant, and comply with detailed requirements.